2022
DOI: 10.1155/2022/8683598
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Analysis of  Raw Material Supply Chain Based on Computational Intelligence

Abstract: With the rapid economic growth and increasingly fierce market competition, the traditional manufacturing advantages have become a thing of the past. There are problems such as inaccurate procurement plans, large quantities of inventory sold out, chaotic procurement processes, and unclear inventory policies. Optimizing the procurement of basic raw materials will help reduce raw material costs. This paper analyzes some raw material supply chain processes through the Delphi method, Plato principle, and trend-adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Table 5 displays the open coding for triggers and how they were combining to a significant axial theme, while Table 6 displays the technological inhibitors of AI implementation. (Bag et al, 2021b, Jamwal et al, 2022 Supply risk management (Liu, 2022, Cavalcante et al, 2019 Supply chain collaboration (Li et al, 2001) Supply network performance and optimization (Chan and Chan, 2004, Narwane et al, 2021, Choy et al, 2002, Dubey et al, 2020, Bourke, 2019, Che et al, 2022, Dong, 2022, Kasie et al, 2017 This research identified three primary codes, namely environmental sustainability, social responsibility, and governance. The code of 'environmental sustainability' encompasses a range of environmentally beneficial practices, such as achieving net-zero emissions, adopting circular economy principles, reducing waste, and promoting environmentally sustainable production.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Table 5 displays the open coding for triggers and how they were combining to a significant axial theme, while Table 6 displays the technological inhibitors of AI implementation. (Bag et al, 2021b, Jamwal et al, 2022 Supply risk management (Liu, 2022, Cavalcante et al, 2019 Supply chain collaboration (Li et al, 2001) Supply network performance and optimization (Chan and Chan, 2004, Narwane et al, 2021, Choy et al, 2002, Dubey et al, 2020, Bourke, 2019, Che et al, 2022, Dong, 2022, Kasie et al, 2017 This research identified three primary codes, namely environmental sustainability, social responsibility, and governance. The code of 'environmental sustainability' encompasses a range of environmentally beneficial practices, such as achieving net-zero emissions, adopting circular economy principles, reducing waste, and promoting environmentally sustainable production.…”
Section: Thematic Analysismentioning
confidence: 99%
“…The use of advanced technologies like BMIS aligns with the broader trend of strengthening supply chain management through technology, which involves utilizing sensors like RFID, CRM, AI, and ML to collect information at every checkpoint in the supply chain process [8]. This shift towards digital solutions reflects the need for businesses to innovate and adapt to the evolving complexities and expectations within the industry [9].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of research aims to measure the effectiveness of the traditional exponential smoothing method compared to an informed criterion-based approach in selecting forecasting methods. With a better understanding of the strengths and limitations of the exponential smoothing method, organizations can make better decisions in business planning, reduce purchasing costs, optimize inventory, and create a win-win situation with suppliers (Dong, 2022).…”
Section: Introductionmentioning
confidence: 99%